Stability of vitamin C in broccoli at different storage conditions - Nasser Al-Habsi; Sithara Suresh; Amani Al-Yhmedi; Marwa Al-Shoryani; Mostafa I. Waly; Mohammad Shafiur Rahman (International Journal of Food Studies)
In this study, the retention of vitamin C in fresh broccoli stored at different temperatures (i.e. chiller, room, cooking, and roasting or baking; 5-120oC) was investigated. The thermal stability of vitamin C in broccoli was analysed at 5, 20, 45, 60, 70, 80, 110, and 120oC. The vitamin C content was measured by the indophenol titration method. Vitamin C was affected negatively at all stored temperatures. The degradation of vitamin C was modelled by first-order reaction kinetics and the reaction rate constants were observed as 9.03Ö10−8 and 5.65Ö10−3 s −1 when stored at 5oC and 120oC, respectively. The activation energy was estimated as 74.2 kJ/mol within the temperature range used in this study. The lowest decay of vitamin C was observed during the chilling condition. The data on retention of vitamin C in broccoli could be used to determine their stability, when stored as raw, and when heated at different temperatures.